Beauveria bassiana and Metarhizium anisopliae as compatible and efficient controllers of plague insects in aquaponic crops (Scientia Agropecuaria, 2020)
The objective was to study the compatibility and efficiency of Beauveria bassiana and Metarhizium anisopliae for the control of insect pests in cabbage and lettuce grown in an aquaponic system made up of Piaractus brachypomus tanks. Spore solutions of B. bassiana and M. anisopliae were prepared. The data submitted to a Completely Random Design, with four treatments, three repetitions and the averages compared by the 5% Tukey test showed that B. bassiana + M. anisopliae caused 73% mortality of Bemisia tabaci on the underside of the lettuce leaves, B. bassiana revealed 84% mortality for Brevicoryne brassicae L. in the bundle of cabbage leaves in 23 days. On the underside of cabbage leaves, B. bassiana + M. anisopliae, showed 79% mortality in just 6 days and M. anisopliae 88% in 23 days after application. The entomopathogenic fungi B. bassiana + M. anisopliae evaluated were effective for the control of whitefly on the underside of lettuce leaves. B. bassiana was more effective in controlling beam aphids and M. anisopliae on the underside of cabbage leaves during the second application.
Keywords: Beauveria bassiana; Metarhizium anisopliae; plagues insects; vegetables; aquaponic system.